Sex-dependent association of DNA methylation in the coding region of the corticotropin-releasing hormone gene and schizophrenia spectrum disorder - Lili Qing; Peng Xiong; Yumei Lu; Hongyan Jiang; Shengjie Nie (Taylor & Francis Group, 2023)
Background Schizophrenia spectrum disorder (SSD) is a common mental disorder causing severe and chronic disability. Epigenetic changes in genes related to the hypothalamic-pituitary-adrenal (HPA) axis are believed to play an important role in SSD pathogenesis. The methylation status of the corticotropin-releasing hormone (CRH) gene, which is central to the HPA axis, has not been investigated in patients with SSD. Aim We investigated the methylation status of the coding region of the CRH gene (hereafter, CRH methylation) using peripheral blood samples from patients with SSD. Subjects and methods We used sodium bisulphite and MethylTarget to determine CRH methylation after collecting peripheral blood samples from 70 patients with SSD who had positive symptoms and 68 healthy controls. Results CRH methylation was significantly increased in patients with SSD, especially in male patients. Conclusions Differences in CRH methylation were detectable in the peripheral blood of patients with SSD. Epigenetic abnormalities in the CRH gene were closely related to positive symptoms of SSD, suggesting that epigenetic processes may mediate the pathophysiology of SSD.